Analysis of the Effect of Gross Regional Domestic Product, Labor Force Participation Rate and Unemployment on Poverty in North Sumatra Province in 2001-2020 - Damayanti, Dewi Rahma; Utami, Gelis Septia; Dwifany, Vera (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of Gross Regional Domestic Product (GRDP), Labor Force Participation Rate (TPAK) and Unemployment on poverty in North Sumatra Province in the period 2001-2020. Multiple linear regression analysis method is the method used in this study with the use of secondary data sourced from BPS. The results of this study show that partially there is an influence between unemployment and poverty and there is no effect of GRDP and TPAK on Poverty in North Sumatra Province. And simultaneously the variables GRDP, TPAK and unemployment jointly affect poverty in North Sumatra Province.